Horn-like space-coiling metamaterials toward simultaneous phase and amplitude modulation - Reza Ghaffarivardavagh (Nature Portfolio, 2018)
Acoustic metasurfaces can be used to control acoustic waves, but generally they focus on phase control which limits potential functionality. Here, Ghaffarivardavagh et al. analytically develop a horn-like space coiling acoustic metasurface to control both the amplitude and phase of acoustic radiation patterns.